CLIMATE CHANGING IMPACT ON RICE PRODUCTION - Fitriani Fitriani (Politeknik Negeri Lampung, 2017)
Rice is the staple food of Indonesian society. The national rice production capability depends not only on the technical and economic aspects of production but also on the environmental carrying capacity, especially the availability of adequate rainfall and climate. The cyclical changes of extreme climate that occur affect the performance of national rice production. This study aims to determine the impact of extreme climate on national rice production. The research method used linear regression with El Nino (D1) and La Nina (D2) as extreme dummy extreme free variable and national rice production as its bound factor. The data used are based on BPS Indonesia with the duration of 1980-2011. The analysis shows that the presence of cyclically extreme climate has a significant effect on national rice production. Climate change has a negative and positive impact on rice production. El-Nino has a negative impact, while La Nina is the opposite. The difference in the size of the impact of climate change can be seen from the slope difference in the variable coefficient.Â Key words: climate changing, El-Nino, La-Nina, production, rice